(untitled) (Studia Prawnicze / The Legal Studies, 2010)
Wolności związkowe stanowią fundament zbiorowych stosunków pracy. Konstytucja RP w art. 12 gwarantuje wolność tworzenia i działania związków zawodowych. W doktrynie akcentuje się różnice między wolnościami i prawami. Przez pojęcie wolności związkowych rozumie się swobody i przywileje nie uregulowane bezpośrednio w drodze ustawowej, choć prawo ustawowe wyznacza granice wolności przysługujące jednostkom i ich zbiorowością. Nawet zatem przy braku wyraźnych podstaw w prawie ustanowionym przez organy państwa wolności te są akceptowane przez władze publiczne, a w obszarze zbiorowego prawa pracy także przez partnerów społecznych. Państwo nie jest dysponentem wolności związkowych, a jego rola sprowadza się jedynie do wyznaczenia granic korzystania z tych wolności. W związku z tym w doktrynie wolności związkowe są rozumiane jako zabezpieczenie organizacji związkowych i pracodawców przed władzą państwową, która nie może pozbawić ich praw zagwarantowanych w art. 59 konstytucji RP. One of indisputable freedoms of labor unions is the freedom of coalition. Under Labor Unions Act, full right to coalition consists of: freedom to establish labor unions and freedom to join existing labor unions. In Poland some social and labor groups were deprived of the freedom of coalition (full or even limited), which is not consistent with international and European law. For instance, employers (outworkers) due to the fact that they are not employees within the meaning of art. 2 of the Labor Code, cannot establish labor unions, even though they perform similar type of work as teleworkers (outside work premises) who enjoy full right of coalition just as all other employees. There are also justified doubts if it is right that Polish law-maker refused to grant the freedom to establish and join labor unions by freelancers and those who perform work on the basis of civil-law agreements. Granting them at least limited right of coalition would correspond to art. 1 of the Labor Union Act that defines labor unions as organizations of people who perform work, not only those who are employed. Art. 78 par. 6 of the Act on Civil Service of 2008 forbids members of civil service who are high in hierarchy to serve any function in labor unions. Undoubtedly, some persons employed in the field of civil service who are high in hierarchy fulfill premises provided in Convention No. 151 of International Labor Organization which allows for restriction of labor union freedoms in the said respect, yet that does not concern all people. Depriving judges of freedom of coalition when it comes to establishment of labor unions and joining already existing ones is also contrary to Conventions No. 87 and 151 of the International Labor Organization. The judges neither can be perceived as workers employed on high positions, engaged in creation of politics nor employers whose competences are mostly of confidential character. The rule concerning restriction of freedom of coalition in case of policemen and prison officers may also create some justified doubts in relation to art. 9 of the Convention No. 87 of the International Labor Organization. Thus, the law-maker’s actions should aim at expanding the subjective scope of the freedom of coalition through abolition of numerous restrictions related to that freedom in order to adjust Polish national solutions in that area to international and European law. Still not all entitled persons use the freedom of coalition in full, or even limited scope.